MAKHDUM JA`FAR BUBAKANI AND HIS PERSPECTIVE ON EPISTEMOLOGY: AN OVERVIEW IN THE LIGHT OF HIS BOOK: NAHJ-UL-TA`LLUM - Dr. Abdul Ghaffar Madani; Dr Muhammad Israel Khan; Dr Salahuddin; Khawaja Arshid Ali; Sabir Ali; Saba Ghizali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This paper analyzes the Bubakani`s view on Islamic education through the Nahj-ut-tallum. Makhdum Ja`far Bubakani (d. 1002 A.H) was one of the most eminent Islamic scholars and earlier pioneer educationists of Sindh in sixteenth century A.H. His great contributions are immense and overwhelming in the field of education. He wrote two books on the concept of Islamic education and educational system according to the Islamic perspectives. His first unpublished book Nahj-ut-tallum, (the method of education) and he summarized in his Persian version known as Hasil-ul-nahj (A digest of Nahj). In Nahj-ut-Ta`llum, Makhdum Ja`far Bubakani provides details about the meaning of knowledge, wisdom, jurisprudence and excellence of knowledge. He further identifies the intention behind acquiring knowledge. He categorized the knowledge in three major types, i.e. Uloom-e-Sharia, Uloom-e-Adbia (literary sciences) and Uloom-e-Hikmia (Natural science and philosophy). Furthermore, he suggested the authentic books as a reference to the context to the types of knowledge. He presented his argumentation on the various Islamic syllabuses. He collected the noble pearls and etiquette for teachers and students, and also incorporated some basic principles of knowledge for learners and teachers. He discussed some other important principles of accruistion of knowledge and destructive factors of that tend to astray them to acquire them to acquire knowledge. This brief study introduces as well as explores a profound manuscript on Islamic epistemology. It is also an attempt to investigate the concept, perspective, aim and objectives and the sources of his book.